Characterization of zircon reference materials via high precision U–Pb LA-MC-ICP-MS. Issue 10 (1st September 2017) - Lana, Cristiano; Farina, Federico; Gerdes, Axel; Alkmim, Ana; Gonçalves, Guilherme O.; Jardim, Antonio C.
Abstract : Recent improvements in laser ablation and multicollector (MC)-ICP-MS technology offer higher sensitivity, robust stability, and larger dynamic ranges. Abstract : Recent improvements in laser ablation and multicollector (MC)-ICP-MS technology offer higher sensitivity, robust stability, and larger dynamic ranges. Such advances are translated into improved accuracy and precision on U–Pb age determinations, reduced spot sizes for high spatial resolution and reliable corrections for any amount of common Pb (Pbc ). Although a number of studies have focused on the high-spatial resolution of the LA-MC-ICP-MS method, comparatively fewer experiments have explored the precision and stability of multi-collector instruments for high-precision U–Pb geochronology. In this contribution, we describe the precision and accuracy of Pbc corrected U–Pb ages obtained by LA-MC-ICP-MS, and discuss the homogeneity of two batches of zircon megacrystals (the Rio do Peixe (RP) and Blue Berry (BB)) as potential reference materials. The enhanced sensitivity and stability of the LA-MC-ICP-MS system allowed the determination of apparent Pb/U and Pb/Pb ratios with uncertainties of 0.3 to 1% (2s) for nearly all reference materials available. The measurements are done in automated mode, with a spatial resolution of 20 μm-wide spots. The short- and long-term reproducibility of 206 Pb/ 238 U, 207 Pb/ 235 U and 207 Pb/ 206 Pb ratios were assessed based on several reference materials, including GJ-1 (96 analyses), M125 (96 analyses), Temora (34 analyses), 91500 (29 analyses), FC-1 (17 analyses), BB (121 analyses) and Plešovice (133 analyses). The results show that the accuracy and precision of the relevant ratios are often between 0.5 and 1.0% (RSD). U–Pb LA-MC-ICP-MS and TIMS dates of four new megacrystals of the BB zircons agreed within error at ca. 560 ± 1 Ma, and demonstrate that they constitute suitable reference materials for LA-ICP-MS analyses. U–Pb LA-MC-ICP-MS for the RP zircons revealed low concentrations of U and Pb and a scattering of ages from 580 to 600 Ma (mean of 593 ± 5 Ma). The RP zircons may only be suitable as a quality control reference material.